Proposta metodológica para a produção de hipervídeos educativos em cursos on-line de capacitação profissional: o caso do curso biossegurança e boas práticas laboratoriais da Difop/Codec/Progep/UFC - Portela, Karine Nascimento (2023)
Online teaching is characterized by its dependence on the use of information and communication technologies (ICT) due to the physical and/or temporal distance between teachers and students. One of these technologies is video lessons, which are ways of transmitting information linearly, with little or almost no possibility of intervention by the student/viewer. On the other hand, hypervideos (HV), known as interactive videos, are now available on the internet. In addition to the basic controllers of linear videos (play, stop, fast forward and rewind), they present additional content (in the form of text, image, audio, hyperlink etc.), alternative browsing and options for users to insert new content. This research set out to develop a methodology for the production of educational HVs in an online professional training course, using as a case the online training course in Biosafety and Good Laboratory Practices run by Difop/Codec/Progep/UFC. In order to achieve this objective, an empirical, qualitative and descriptive study was carried out in the form of a case study. The locus of the research was the Professional Training Division (Difop), linked to the Development and Career Coordination (Codec) of the Pro-Rectory for People Management (Progep) of the Federal University of Ceará (UFC). The participants were the four educational technicians (TAE) and the instructor of Difop’s Biosafety course. The data was obtained from two focus groups with the TAEs and two semi-structured interviews with the Biosafety course instructor. The data was processed using content analysis. As a result, we obtained: 1) a mapping of the video production process at Difop, especially the Biosafety course, in which we identified the recording approaches, the production stages, the team members and their roles, the limitations and the structural, technical and technological challenges of the context; 2) the development of a methodological proposal for creating educational videos, presented in a guide in the format of an interactive flipbook: Hypervideo Creation Guide (the product of the research); and 3) the evaluation of the methodology developed, in terms of its usefulness, applicability and acceptability from the subjects’ perceptions. We can conclude, after completing this research, that the methodology developed in this study made it possible, from pre-production to post-production, to direct the technical-pedagogical actions of the Difop team in creating HVs for the Biosafety course, using accessible language, presenting a set of information, approaches, instruments and tools for flexible application, as a way of enhancing the steps, instruments and knowledge already present in the context of the creation of interactive video lessons.